2017
DOI: 10.1051/0004-6361/201630038
|View full text |Cite
|
Sign up to set email alerts
|

X-ray orbital modulation of a white dwarf accreting from an L dwarf

Abstract: In an XMM-Newton observation of the binary SDSS J121209.31+013627.7, consisting of a white dwarf and an L dwarf, we detect X-ray orbital modulation as proof of accretion from the substellar companion onto the magnetic white dwarf. We constrain the system geometry (inclination as well as magnetic and pole-cap angle) through modelling of the X-ray light curve, and we derive a mass accretion rate of 3.2 × 10 −14 M /yr from the X-ray luminosity (∼3 × 10 29 erg/s). From X-ray studies of L dwarfs, a possible wind dr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…The accretion rates in period-bounce systems are low enough that they could appear similar to detached systems. There is some evidence from X-ray observations that SDSS J1212+0136 may be Roche-lobe filling (Stelzer et al 2017), which lends support to this interpretation. Therefore, these systems may form a distinct population from the longer period detached magnetic white dwarf binaries that have been the focus of this paper.…”
Section: Evolutionary Statusmentioning
confidence: 80%
“…The accretion rates in period-bounce systems are low enough that they could appear similar to detached systems. There is some evidence from X-ray observations that SDSS J1212+0136 may be Roche-lobe filling (Stelzer et al 2017), which lends support to this interpretation. Therefore, these systems may form a distinct population from the longer period detached magnetic white dwarf binaries that have been the focus of this paper.…”
Section: Evolutionary Statusmentioning
confidence: 80%
“…In the case of SDSS J1212+0136, early studies suggested that the brown dwarf was under filling its Roche lobe and was more likely to be a PREP than a LARP (Schmidt et al 2005;Farihi et al 2008). However, the X-ray observations of Stelzer et al (2017) strongly suggest that this system may be filling its Roche lobe and should be considered a LARP.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, ∼10 WDs accreting from brown dwarfs have been reported (Longstaff et al 2019). Only two of them show X-ray emission, EF Eridani (Schwope et al 2007) and SDSSJ121209.31+013627.7 (Stelzer et al 2017); however, both are cool WDs with effective temperatures lower than 10,000 K, and both are polars whose strong magnetic fields channel material from the companion to the WDs' magnetic poles to be accreted. The three WDs with hard X-ray emission reported in this paper have much higher effective temperatures than these polars.…”
Section: Accretion From a Hidden Companionmentioning
confidence: 99%